Shear assisted processing and extrusion of enhanced strength aluminum alloy tubing. (October 2021) - Taysom, Brandon Scott; Overman, Nicole; Olszta, Matt; Reza-E-Rabby, Md; Skszek, Tim; DiCiano, Massimo; Whalen, Scott
Abstract: Shear Assisted Processing and Extrusion (ShAPE) enables the extrusion of many alloys with enhanced properties. In this study, ShAPE was used to extrude tubes of aluminum alloy 6063 measuring 12 mm in diameter at extrusion speeds up to 3.8 m/min, an increase of 10 times over what has previously been reported for ShAPE. Increasing the extrusion speed from 0.7 to 3.8 m/min resulted in using 68% less process energy at steady state without any loss in mechanical properties. As-extruded tubes had ultimate tensile strengths on par with conventional T5 extrusions and double the elongation at break. ShAPE extruded tubes that underwent a T5 heat treatment had yield and ultimate strengths of 198 and 234 MPa, respectively, which is ~30% higher than standard T5 material and comparable to T6 properties. Microstructural analyses were performed on as-extruded and T5 treated tubes. Grain refinement below 20 μm was identified, with no detectable growth of macroscale Mg2 Si strengthening precipitates. Nanoscale β″ was not observed in the as-extruded materials but was prominent after T5 heat treatment suggesting that β″ strengthening precipitates were solutionized in situ during the ShAPE process. The ability to perform solution heat treating in situ, rather than post-extrusion, eliminates an energy intensive process step and is applicable to a wide variety of alloys. Graphical abstract: Image 1 Highlights: Shear Assisted Processing and Extrusion (ShAPE) was used to produce AA 6063 tubing. Maximum extrusion speeds of 3.8 m/s were achieved, over 10 times faster than any previous friction extrusion. Energy efficiency increased with extrusion speed, reaching up to 42% at steady state. ShAPE Extrusions with a T5 heat treatment achieved mechanical properties on par with a traditional T6 heat treatment. ShAPE + T5 resulted in peak to slightly over-aged microstructure, similar to a conventional T6 microstructure.